Pengaruh Literasi Ekonomi, Literasi Digital dan Motivasi Belajar Terhadap Prestasi Belajar Siswa Mata Pelajaran Ekonomi SMAN 2 Gunung Talang (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the influence of economic literacy and digital literacy on student learning motivation in economics class X at SMAN 2 Gunung Talang, analyzing the influence of economic literacy, digital literacy and learning motivation on student learning achievement in economics class X at SMAN 2 Gunung Talang. The research conducted was associative deceptive research. The population is all students of class X of SMAN 2 Gunung Talang, with a proportional random sampling sample drawn of 112 people. Data analysis using descriptive and inductive analysis using pathway analysis. The results of the study show that economic literacy has a positive and significant effect on students' learning motivation in economics class X at SMAN 2 Gunung Talang. Digital literacy has a positive and significant effect on students' learning motivation in Talang economics subjects. Economic literacy has a positive and significant effect on student learning achievement in economics subjects. Digital literacy has a positive and significant effect on student learning achievement in classroom economics subjects. Learning motivation has a positive and significant effect on student learning achievement in economics subjects